Maize Transposable Elements Ac/Ds as Insertion Mutagenesis Tools in Candida albicans. Issue 4 (1st April 2018) - Mielich, Kevin; Shtifman-Segal, Ella; Golz, Julia C; Zeng, Guisheng; Wang, Yue; Berman, Judith; Kunze, Reinhard
Abstract: In nonmodel systems, genetic research is often limited by the lack of techniques for the generation and identification of gene mutations. One approach to overcome this bottleneck is the application of transposons for gene tagging. We have established a two-element transposon tagging system, based on the transposable elements Activator ( Ac )/ Dissociation ( Ds ) from maize, for in vivo insertion mutagenesis in the fungal human pathogen Candida albicans . A nonautonomous Ds transposon carrying a selectable marker was constructed into the ADE2 promoter on chromosome 3 and a codon usage-adapted Ac transposase gene was inserted into the neutral NEUT5L locus on chromosome 5. In C. albicans cells expressing the transposase, the Ds element efficiently excised and reintegrated elsewhere in the genome, which makes the Ac / Ds transposons promising tools for saturating insertion mutagenesis in clinical strains of C. albicans .